Implementasi Konsep “/nspire” dalam Perancangan Interior Digital Startup Exhibition and Training Center di Surabaya - Favian Grady Susanto; Diana Thamrin; Celline Junica Pradjonggo (Intra, 2019)
In recent years, Indonesia has entered a new era in infrastructure, Industry 4.0. This new era brings Indonesia to a digital, connected lifestyle. This is the spark that lights the rising of unicorns such as “Go-Jek”, Tokopedia”, “Traveloka”, and “Bukalapak”. This new lifestyle also brings Indonesia to solve national problems through digital solutions. But in reality, the Indonesian youth is not trained and educated in an efficient enough environment. On this foundation, the designer proposes an Interior Design of a Digital Startup Exhibition and Training Center in Surabaya, a facility built to inspire and train digital startup activist to support the vision of Surabaya as a smarter city. The design use “/inspire” concept, a combination of “/n”, a code for “beginning” in programming language, and “inspire”, the hope and purpose in which this facility is built on.  The designed facilities include a receptionist for registration, café for refreshments, shop/service area to accommodate user’s needs, exhibition area to showcase digital startup’s community creations, co-working area for working, training room for programming education, seminar/workshop room for various activities, and office for employee. The designer hopes to create a facility that can sufficiently represent and inspire digital startup communities into an influential movement as a digital solution for Indonesia.